PERLINDUNGAN HUKUM TERHADAP KONSUMEN PENGGUNA CREAM WAJAH DOKTER YANG TIDAK MENCANTUMKAN IDENTITAS PRODUK DI KEMASAN (CONTOH KASUS: PUTUSAN MAHKAMAH AGUNG NOMOR 2008 K/PID.SUS/2016) - Sally Irawan; Jeane Neltje Saly (Jurnal Hukum Adigama, 2020)
In Law No.8 of 1999 concerning Consumer Protection Article 4 paragraph (3) states that consumers have the right to obtain correct, clear, and honest information regarding the conditions and guarantees of goods and / or services, but all of this has not been fully achieved as which often occurs in the administration of medicines and face creams by doctors in beauty clinics. Where most beauty clinics provide medicines or face creams to consumers in the absence of clear labels or information about a product. As in the Regulation of the Head of the Drug and Food Supervisory Agency Number 19 of 2015 concerning Technical Requirements for Cosmetics articles 5,6, and 7 which contain clear and correct label markings or information on a product in the package. The type of research used by the writer is normative. To support this research, the author uses the type of literature study research, which examines several documents related to research. The method used is a normative research method using a statutory approach (statue approach) and a case approach (case approach). From the results of the above research, it can be seen that the conclusion is that the implementation of legal protection for consumers who suffer losses due to the absence of clear information marking in a product. The factors that influence the implementation of the labeling of the marking of information are the absence of legal certainty that regulates the inclusion of markings in medic creams.